2006
DOI: 10.1080/02615470500477870
|View full text |Cite
|
Sign up to set email alerts
|

The Support of Adjunct Faculty: An Academic Imperative

Abstract: There is a marked increase in the number of adjunct faculty being hired nationally and internationally, at both the undergraduate and graduate levels, in all academic arenas, including schools of social work. The development and support of adjunct faculty at a school of social work at one flagship university in the United States is discussed and described, including an examination of the issues leading to the increased use of adjuncts; the linkage of adjuncts to tenured faculty in the delivery of classroom tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 6 publications
0
47
0
Order By: Relevance
“…Based on the above, it is not surprising that adjunct faculty are much more likely than full-time faculty to experience feelings of isolation, lack of connectedness to the academic community, and perceptions of marginalization (e.g., Buch & McCullough, 2016;Fagan-Wilen, Springer, Ambrosino, & White, 2007;Forbes, Hickey, White, 2010;Levin & Hernandez, 2014;Webb, Wong, & Hubball, 2013). Other researchers have noted the relationship between these experiences of isolation and the job satisfaction and turnover rates among part-time faculty (e.g., Hoyt, 2012;Meixner & Kruck, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, it is not surprising that adjunct faculty are much more likely than full-time faculty to experience feelings of isolation, lack of connectedness to the academic community, and perceptions of marginalization (e.g., Buch & McCullough, 2016;Fagan-Wilen, Springer, Ambrosino, & White, 2007;Forbes, Hickey, White, 2010;Levin & Hernandez, 2014;Webb, Wong, & Hubball, 2013). Other researchers have noted the relationship between these experiences of isolation and the job satisfaction and turnover rates among part-time faculty (e.g., Hoyt, 2012;Meixner & Kruck, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Though adjuncts have been rated lower than full-time faculty in student evaluations, Fagan-Wilen, Springer, Ambrosino, and White (2006) suggested that these phenomena may be related to a lack of instructional training rather than a lack of content knowledge, as studies comparing student performance on exit exams found no difference in performance between students taught by adjuncts and those taught by full-time faculty. Clark, Moore, Johnston, and Openshaw (2011) concluded that adjuncts need to receive an orientation and continual training in order to prepare them for instruction and make them aware of university policies.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Programs that are more practice-based (business, engineering, health, etc.) have seen an increase in adjunct use (Fagan-Wilen et al, 2006). A study by Magda, et al, (2015) found that the highest percentage of online adjuncts taught business courses (35%), followed by English (29%), general studies (24%), education (22%), psychology (20%), and nursing (15%).…”
Section: Adjunct Faculty Member Roles and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations